Evaluation of Partnership in the Development of Tourist Village in Sidomulyo Village, Batu City - Mariatul Qibtiah; Ach. Apriyanto Romadhan; Ali Roziqin; Saiman (International Research and Development for Human Beings (IRDH), 2025)
The development of tourism villages aimed at improving community welfare often faces challenges such as low resource capacity, poor stakeholder coordination, and inadequate facilities. Specifically in Sidomulyo Village, the existing partnerships have not had a significant impact, raising questions about their effectiveness in supporting the development of village tourism. This research aims to evaluate the partnership program in Sidomulyo Village in order to understand the root of the problems and determine the benefits and shortcomings of the partnership. This research uses a qualitative method with a descriptive approach to highlight the shortcomings and weaknesses in the phenomenon of partnerships. Using the CIPP evaluation model (context, input, process, product), the researcher evaluated the implementation of partnerships in the development of village tourism in Sidomulyo Village, Batu District, Batu City. The research results indicate that the lack of a shared vision in the development of tourism villages is a factor in partnership failure. Therefore, it is hoped that in the future, the parties involved in the development of tourism villages can build a shared commitment to the established vision. Therefore, future research needs to conduct similar studies in different locations to determine if partnership failures are faced with the same factors.